ANALISIS HUBUNGAN PERTUMBUHAN EKONOMI DAN KONSUMSI RUMAH TANGGA PROVINSI RIAU TAHUN 2000-2019 DENGAN ANALISIS VECM - Angelina Morisya; Widayatsari Any; Isbah Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to analyze the relationship between economic growth and household consumption in Riau Province with VECM analysis. The data used in this research is secondary data which is time series. The analytical method used in this research is the Vector Error Correction Model. The results showed that economic growth had a significant negative effect on household consumption in the long and short term and household consumption had a significant positive effect on household consumption in the short term. The results of the impulse response test showed that the shock of economic growth caused household consumption to increase at the beginning of the period, then decreased in the middle of the period, and increased at the end of the period. Then, the household consumption shock causes economic growth to decline at the beginning of the period, then increases in the middle of the period, and decreases at the end of the period. The results of the variance decomposition show that the contribution of economic growth to changes in household consumption by the end of the period is 57.44%. This condition indicates that economic growth has an effect on household consumption. Meanwhile, household consumption contributed 27.02% to changes in economic growth until the end of the period. The results of the Granger causality test showed that there was a one-way relationship, namely that economic growth had an effect on household consumption. The results of the Johansen cointegration test indicate a long-term relationship between variablesKeyword: economic growth, household consumption, impulse response, variance decomposition, Granger causality, Johansen test, VECM